Respostas
respondido por:
1
olá!
f(x) = 3x² - 4x + 1
f(x) = 1
1 = 3x² - 4x + 1
1 - 1 = 3x² - 4x
0 = 3x² - 4x
3x² - 4x = 0
x(3x - 4) = 0
x = 0
também podemos ter;
3x - 4 = 0
3x = 4
x = 4/3
x`= 0 e x`` = 4/3
espero ter ajudado!
f(x) = 3x² - 4x + 1
f(x) = 1
1 = 3x² - 4x + 1
1 - 1 = 3x² - 4x
0 = 3x² - 4x
3x² - 4x = 0
x(3x - 4) = 0
x = 0
também podemos ter;
3x - 4 = 0
3x = 4
x = 4/3
x`= 0 e x`` = 4/3
espero ter ajudado!
hpprandreia:
obrigado
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás